Interchange and market in the critical thought of Pierre Bourdieu (2011)
This article contains the contributions to the theory of interchange and market of Pierre Bourdieu and also of some specialists concerned in the work of the French sociologist. The text approaches the point of view of Bordieu as a critical thinker that is social and politically engaged, who sought to question the logic of the structures of interchange and the market inWestern society, and revealed how they have become omnipresent units in the global culture life. His work allows us to understand the lattice of relations in which the dynamics of trade and market in the capitalist system are suspended.